Factors Affecting Patterns of Fast Food Consumption in Students of Medical Study Program Faculty of Medicine Tanjungpura University - Carla Jean Marshellina; Agustina Arundina Triharja Tejoyuwono; Abror Irsan (Faculty of Medicine, Universitas Jember, 2023)
Medical students who are in their late teens and are affected by high stress due to academic loads experience changes in nutritional intake behavior, namely changes in eating patterns with a tendency to consume fast food (fast food). The purpose of this study was to determine the factors that influence fast food consumption patterns in students of the Medical Study Program, Faculty of Medicine, Tanjungpura University. This study uses a type of observational analytic research with a cross-sectional design. This study used data on weight and height measurements, a 3x24-hour Food Record, and a questionnaire on 46 students of the Medical Study Program class of 2022. The results showed low consumption of calories, protein and carbohydrates, and high consumption of fat. The overall average intake of energy, fat and carbohydrates is normal, while protein intake is low. There is no effect of all variables on consumption of energy, protein, fat, carbohydrates, and nutritional status. However, action on fast food has a significant effect on energy consumption. Students often consume fast food which is processed by frying process. Low protein intake and high fat consumption indicate the need for education for food selection in reducing the negative impact on the health of medical students. Keywords: Fast food, medical students, consumption patterns, factors